2019
DOI: 10.1186/s40497-019-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of intellectual capital in augmenting the start-up intentions of Indians—an analysis using GEM data

Abstract: Purpose: Although the intellectual capital (IC) has already received much attention from the researchers in the field of innovation performance, there is still a paucity in the measuring of the role of IC in venture creation. The present study is an attempt to examine the influence of IC on start-ups. Methodology: In this study, a large data set of 3360 respondents from India provided by the largest entrepreneurship research project GEM has been used. A logistic regression technique has been applied to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Researchers are showing an increased interest in exploring the GEM data sets (Arafat et al, 2019; Arenius & Minniti, 2005; Autio et al, 2013; Bakar et al, 2017; Cetindamar et al, 2012; Davidsson & Honig, 2003; Khan et al, 2019a; Langowitz & Minniti, 2007; Tsai et al, 2016). The objective of our study is to examine the impact of social legitimacy on the intention to create new ventures (Khan et al, 2021), and the data provided by the GEM APS is in congruence with the objective of our study; hence, we have used the APS part of GEM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are showing an increased interest in exploring the GEM data sets (Arafat et al, 2019; Arenius & Minniti, 2005; Autio et al, 2013; Bakar et al, 2017; Cetindamar et al, 2012; Davidsson & Honig, 2003; Khan et al, 2019a; Langowitz & Minniti, 2007; Tsai et al, 2016). The objective of our study is to examine the impact of social legitimacy on the intention to create new ventures (Khan et al, 2021), and the data provided by the GEM APS is in congruence with the objective of our study; hence, we have used the APS part of GEM.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on students limit the generalisation. Some other studies have also measured the influence of intellectual capital on start-up behaviour (Arafat et al, 2020c;Khan et al, 2019aKhan et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…According to Khan et al (2019), the higher one's level of education the lower their intention to participate in an entrepreneurial start-up. Drawing on Morris et al (2006), we include education attainment as a categorical variable, differentiating between undergraduates (who have not yet received a bachelor's degree) and postgraduates (who continue studying by pursuing a master's degree or a doctorate).…”
Section: The Moderating Effect Of Demographicsmentioning
confidence: 99%
“…However, Ozaralli and Rivenburgh (2016) argued that as entrepreneurs become older, their intention to start their own business becomes more pronounced. Additionally, men seem to be more open to entrepreneurial training (Harris & Gibson, 2008), and individuals with higher education attainment seem to have lower EI (Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The significant role that entrepreneurship plays in enhancing socio-economic evolution in both developed and developing countries is widely discussed in the literature (Faggio and Silva, 2014; Cui et al , 2019; Ahmed et al , 2020; Elnadi and Gheith, 2021). The idea of entrepreneurial intention (EI) is vital for the area of entrepreneurship development and can frequently be seen in studies related to entrepreneurial behaviour (Ahmad et al , 2014; Györfy, 2014; Khan et al , 2019; Dileo and García Pereiro, 2019; Bilgiseven and Kasimoǧlu, 2019). Arafat and Saleem (2017) investigated the factors that affect the decision to start a new business among Indians and concluded that gender, perceived opportunities, self-efficacy and risk perception are the major determining factors for establishing a new business in India.…”
Section: Introductionmentioning
confidence: 99%